Biting on customized mouthguards improves vertical jump and slider quality of baseball pitchers - Teng, N.-C.; Hu, H.-S.; Wu, T.-I.; Shiu, Y.-J.; Yen, C.-W.; Chan, W.-J.; Chiu, C. H. (The Journal of Strength and Conditioning Research, 2025)
The concurrent activation potentiation induced by biting on customized mouthguards may improve strength performance. The purpose of this study is to investigate whether the use of customized mouthguards is effective in improving the athletic performance of baseball pitchers and further improving the sharpness of fastball and breaking balls. Ten professional (age: 20.50 ± 1.08 years; height: 177.6 ± 4.7 cm; body mass: 77.7 ± 9.6 kg) baseball pitchers were recruited and randomly divided into customized mouthguards trial (MG) and control trial (N-MG) without wearing customized mouthguards. Subjects were tested for bite force, grip strength, counter movement jump, and pitching tests after wearing mouthguards (MG trial) and without mouthguards (N-MG trial). The bite force was significantly higher in the MG trial than in the N-MG trial (MG: 1,512.5 ± 531.7 N; N-MG: 1,159.1 ± 407.0 N; p = 0.014; Cohen's d = 0.75). The spin rate of sliders was significantly higher in the MG trial than in the N-MG trial (MG: 2086.3 ± 243.2 rpm; N-MG:1939.0 ± 312.9 rpm; p = 0.014; Cohen's d = 0.52). The jump height of counter movement jump was significantly higher in the MG trial than in the N-MG trial (MG: 48.8 ± 4.2 cm; N-MG: 47.3 ± 4.0 cm; p = 0.024; Cohen's d = 0.37) with a small effect size. There were no significant differences in grip strength and other pitching parameters. In conclusion, this study demonstrated that customized mouthguards significantly enhanced the bite force of the subjects and augmented the spin rate and the sharpness of the slider.